Evaluation of the presence of Sarcocystis spp. in dogs raised in alpaca farm enterprises in Cajamarca, Peru. - Ydrogo, M. (2025)
The apicomplexans of the genus Sarcocystis are parasites that infect various animal species, including humans. Both dogs and other carnivores can act as definitive hosts of this protozoan. The present study aimed to determine the frequency of Sarcocystis spp. in domestic dogs raised in three alpaca breeding areas in Cajamarca. Random fecal samples were collected from 102 dogs of different ages and both sexes in three locations related to alpaca breeding: Atahualpa Jerusalén Agricultural Workers Cooperative - Cajamarca (N = 35), SAIS Huacraruco - San Juan (N = 33), and Alpacas Project - Foncreagro - Sorochuco (N = 34). The samples were processed using the Sheather flotation technique. Through microscopic observation, ellipsoidal, light gray sporocysts with average dimensions of 13.87±1.61 µm in length and 9.12±1.05 µm in width were identified. In the data analysis, an overall frequency of Sarcocystis spp. of 42.16% (95% CI: 32.57 - 51.74) was determined, with a higher presence in the dogs from Huacraruco (PSarcocystis spp (P>0.05). In conclusion, this study reveals a high prevalence of Sarcocystis spp. in domestic dogs from the studied areas in Cajamarca. This emphasizes the pressing need to explore practical and optimal control measures.